The Impact Of Change Management Organizational Innovation In Higher Education Institutions In North Sumatra - Venny Fraya Hartin Nst; Doly Muhendy Wijaya; Azaman, Azaman (Sean Institute, 2025)
This study aims to analyze the influence of change management on organizational innovation in higher education institutions in North Sumatra. To address these gaps, higher education institutions need to urgently develop a more adaptive and participatory change management strategy. This strategy should that all parties are involved and supporting the change process towards sustainable innovation. Using qualitative research methods, this study collects data through interviews, observations, and documentation studies in several universities. The results show that effective change management, characterized by transformational leadership, human resource readiness, and technological infrastructure support, contributes significantly to organizational innovation. However, challenges such as resistance to change, limited financial resources, and lack of training for educators remain major obstacles. Therefore, a more adaptive and participatory change management strategy is not just a suggestion, but a necessity for the optimal functioning of organizational innovation.